(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this paper, the author introduces the degenerate Sadik transform and investigates the transform of some elementary functions. Also, sufficient condition for the existence of the said transform is also presented. Furthermore, this paper concludes that degenerate sadik transform is a unification of some other degenerate transforms such as degenerate Laplace transform, degenerate Sumudu transform, degenerate Tarig integral transform, degenerate Elzaki integral transform and Laplace-type integral transform.